Validation of the Wexner scale in women with fecal incontinence in a Turkish population - AY, NADİYE PINAR (SPRINGER LONDON LTD, 2011)
Introduction and hypothesis The main aim of this study was to validate the Turkish translated version of the Wexner scale. Methods After establishing the test-retest reliability and internal consistency of the Turkish version of Wexner scale on 31 patients, total and subscale scores and anal manometric measurements of 60 participants were performed. Correlation between Wexner scale scores and manometric measurement values were analyzed and those values of patients with or without anal incontinence symptoms were compared. Results Of the 60 participants, 47 (78%) showed no signs or symptoms of anal incontinence. Wexner scale showed a high internal consistency (Cronbach's alpha=0.816). Total and each subscale score of Wexner scale showed strong correlation with resting and maximal squeeze pressures and between each other (p<0.005). The pressure values were significantly less in asymptomatic patients compared to patients with any degree of symptoms (p<0.05). Conclusion The Turkish translated version of the Wexner scale is a reliable, consistent, and valid instrument to evaluate anal functions in women with anal incontinence for Turkish speaking women. Total and subscale scores of the Wexner scale and anal manometric measurements showed significant correlation.
Keywords: Wexner scale; Turkish version; Anal incontinence; ANAL INCONTINENCE; VAGINAL DELIVERY; PREVALENCE